Model Catalytic Studies on the Thermal Dehydrogenation of the Benzaldehyde/Cyclohexylmethanol LOHC System on Pt(111) - Schwaab, Valentin; Hemauer, Felix; Steffen, Julien; Waleska-Wellnhofer, Natalie; Marie Freiberger, Eva; Steinmetz, Marius; Görling, Andreas; Wasserscheid, Peter; Steinrück, Hans-Peter; Papp, Christian (Chemistry - A European Journal, 2024)
We investigated the dehydrogenation reaction and the thermal robustness of the liquid organic hydrogen carrier (LOHC) couple benzaldehyde/cyclohexylmethanol on a Pt(111) model catalyst in situ in synchrotron radiation photoelectron spectroscopy- and complementary temperature-programmed desorption experiments. The system stores hydrogen in a cyclohexyl group and a primary alcohol functionality and achieves an attractive hydrogen storage capacity of 7.0 mass %. We observed a stepwise dehydrogenation mechanism, characterized by a low temperature dehydrogenation of the alcohol group at 235 K. However, stability limitations challenge the system's application as reversible hydrogen storage solution, as the resultant aldehyde was found to decompose during the dehydrogenation of its cyclohexyl group (between 250 and 350 K). A comparison of cyclohexylmethanol with the structurally related secondary alcohol (1-cyclohexylethanol; 6.3 mass % hydrogen) revealed a parallel stepwise dehydrogenation pattern for both compounds, but a technically relevant superior thermal robustness of the latter, demonstrating the influence of the alcohol-group's substitution degree on the dehydrogenation characteristics of alcohol-functionalized LOHCs. Density functional theory calculations are in agreement with the experimentally observed stability trend.
CRIS-Team Scopus Importer:2024-12-06
Keywords: Alcohols; Benzaldehyde; Cyclohexylmethanol; Liquid Organic Hydrogen Carriers (LOHCs); Surface Reactions